Effects of atropine on the release of newly synthesized acetylcholine from rat striatal slices at various concentrations of calcium ions - Dolezal, V; Tucek, S (Neurochemical research, 1990)
The release of acetylcholine (ACh) from brain tissue is known to be inhibited by muscarinic autoreceptors on cholinergic nerve terminals but the mechanism of the inhibition is not understood. Atropine brings about an increase of ACh release by removing the inhibitory action of autoreceptors. We investigated whether the effect of atropine on the release of [14C]ACh newly synthesized during incubations from [U-14C] glucose depends on the concentration of Ca2+ in the medium. In rat striatal slices incubated in the presence of an inhibitor of cholinesterases and of 30 mmol/l K+, significant increases in the release of [14C]ACh elicited by atropine were only observed during incubations with very low concentrations of Ca2+. This finding supports the view that the activation of presynaptic muscarinic autoreceptors in the brain affects the release of ACh by reducing the availability of Ca2+ that is required for transmitter liberation.
Keywords: atropin; inbrední kmeny potkanů; Calcium; vápník; Rats, Inbred Strains; Animals; mužské pohlaví; Rats; In Vitro Techniques; zvířata; Acetylcholine; techniky in vitro; Corpus Striatum; Male; Atropine; krysa rodu Rattus; corpus striatum; acetylcholin